Case Report: MYH9-related disease caused by Ala44Pro mutation in a child with a previous diagnosis of chronic immune thrombocytopenia - Niwa, Kaori; Toyoda, Hidemi; Kohso, Atsushi; Okumura, Yosuke; Kunishima, Shinji; Hirayama, Masahiro (Frontiers in Pediatrics, 2024)
MYH9-related disease, a rare autosomal dominant platelet disorder characterized by thrombocytopenia, giant platelets, and leukocyte inclusion bodies, may mimic immune thrombocytopenia in children unless suspected and carefully excluded. Here, we present a case involving a three-year-old girl with mild bleeding symptoms since infancy, previously diagnosed with chronic immune thrombocytopenia. The patient exhibited isolated thrombocytopenia and lacked any family history of thrombocytopenia, hearing impairment, or renal failure. Examination of peripheral blood smears via light microscopy revealed significant platelet macrocytosis with giant platelets and basophilic Döhle-like bodies in the neutrophils. Subsequent sequencing analysis of MYH9 gene identified a p.Ala44Pro mutation. Throughout a six-year follow-up period, the patient's condition remained stable. Our report underscores the significance of identifying leukocyte inclusion bodies in peripheral blood smears and considering MYH9-related diseases, even in instances of chronic macrothrombocytopenia devoid of familial history or non-hematological manifestations.